2004
DOI: 10.1027/1015-5759.20.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Factor Structure of the Borderline Personality Inventory in Adolescents

Abstract: Summary: Borderline personality disorder (BPD) is a frequent disorder in in- and outpatient settings. However, empirical studies suggest that BPD lacks construct validity in adolescents. Problems with validity may be linked to the fact that borderline symptoms can occur in the course of normal adolescence. This study examined the factor structure of borderline symptomatology in a community-based sample of 616 adolescents (mean age = 16.9±1.5). Borderline symptomatology was assessed by the Borderline Personalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 29 publications
6
29
1
1
Order By: Relevance
“…ICC’s were calculated based on one-way random effect models for the unequal number of raters per case, and demonstrated excellent interdiagnostician agreement for BPD dimensional scores (ICC = .91). The prevalence of diagnosable BPD (i.e., ≥ 5 symptom criteria met) at the wave 1 assessment in this sample was 6.8 % (n = 5), which is similar to reported prevalence rates in other community adolescent and mixed-age samples (e.g., 3–6%; (Chabrol et al 2004; Zanarini et al 2011; Zanarini et al 2003). Consistent with previous studies using adolescent samples (Becker et al 2006), intense anger (29 %) and affective instability (28 %) were the most frequently met BPD criteria.…”
Section: Methodssupporting
confidence: 83%
“…ICC’s were calculated based on one-way random effect models for the unequal number of raters per case, and demonstrated excellent interdiagnostician agreement for BPD dimensional scores (ICC = .91). The prevalence of diagnosable BPD (i.e., ≥ 5 symptom criteria met) at the wave 1 assessment in this sample was 6.8 % (n = 5), which is similar to reported prevalence rates in other community adolescent and mixed-age samples (e.g., 3–6%; (Chabrol et al 2004; Zanarini et al 2011; Zanarini et al 2003). Consistent with previous studies using adolescent samples (Becker et al 2006), intense anger (29 %) and affective instability (28 %) were the most frequently met BPD criteria.…”
Section: Methodssupporting
confidence: 83%
“…Two relevant studies have reported prevalence rates of BPD in high school samples. One reported a rate of 6%, and the other 14% (Chabrol, Montovany, Chouicha, Callahan, & Mullet, 2001;Chabrol et al, 2004). It should be noted, however, that the prevalence of BPD was measured by a self-report questionnaire, which may have overestimated the frequency of personality disorders (Emmelkamp & Kamphuis, 2007).…”
Section: Introductionmentioning
confidence: 94%
“…The variation in the prevalence rate estimates across samples of adolescents coupled with the discrepancy in prevalence rates in adolescent versus adult samples raise questions regarding the legitimacy of the diagnosis of adolescent BPD. For example, estimates of prevalence rates in high school and community samples of adolescents vary from 3.3% in a study of 10, 000 11-year olds in the United Kingdom to 14% among 1300 French high school students (Bernstein, Cohen, SchwabStone, Siever, & Shinsato, 1993;Chabrol, Montovany, Chouicha, Callahan, & Mullter, 2001;Chabrol et al, 2004;Zanarini, 2003), while among adolescent inpatient samples the prevalence rate of BPD was found to be between 30% to 53% (Becker, Grilo, Edell, & McGlashan, 2000;Glenn & Klonsky, 2013). Examining sex differences, one study estimated that 76% of individuals who meet criteria for BPD are females (Widiger, & Weissman, 1991).…”
Section: Validity Of Adolescent Bpdmentioning
confidence: 99%